Reactor Core Design and Analysis for a Micronuclear Power Source - Sun, Hao; Wang, Chenglong; Liu, Xiao; Tian, Wenxi; Qiu, Suizheng; Su, Guanghui (Frontiers in Energy Research, 2018)
Underwater Vehicle is designed to ensure the security of country sea boundary, providing harsh requirements for its power system design. Conventional power sources, such as battery and Stirling engine, are featured with low power and short lifetime. Micro nuclear reactor power source featured with higher power density and longer lifetime would strongly meet the demands of unmanned underwater vehicle (UUV) power system. In this paper, a 2.4MWt lithium heat pipe cooled reactor coreis designed for micro nuclear power source, which can be applied for underwater vehicles. The core features with small volume, high power density, long lifetime, and low noise level. Uranium nitride fuel with 70% enrichment and lithium heat pipes are adopted in the core. The reactivity is controlled by 6 control drums with B4C neutron absorber. Monte Carlo code MCNP is used for calculating the power distribution, characteristics of reactivity feedback and core criticality safety. A code MCORE coupling MCNP5 and ORIGEN2 is used to analysis the burnup characteristics of the designed core. The results show that the core life is 14 years, and the core parameters satisfy the safety requirements. This work provides reference to the design and application of the micro nuclear power source.